2013
DOI: 10.1016/j.ijgo.2013.01.018
|View full text |Cite
|
Sign up to set email alerts
|

4D ultrasound evaluation of fetal facial expressions during the latter stages of the second trimester

Abstract: The results indicate that facial expressions can be used as an indicator of normal fetal neurologic development from the second to the third trimester. 4D ultrasound may be a valuable tool for assessing fetal neurobehavioral development during gestation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
38
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(46 citation statements)
references
References 15 publications
7
38
1
Order By: Relevance
“…In the present study using 4D HDlive ultrasound, AGA fetuses between 26 and 37 weeks of gestation demonstrated that mouthing was the most frequent facial expression ( Figure 3A), which is compatible with the previous reports from Japan (Sato et al [14], Kanenishi et al [13], and Yan et al [12]). In contrast to AGA fetus, however, remarkable decrease in the frequency of this mouthing later than 34 weeks in FGR fetuses is the most striking finding in our current study (Tables 5B and 6B, Figures 4B and 5B).…”
Section: Page 7 Ofsupporting
confidence: 93%
See 4 more Smart Citations
“…In the present study using 4D HDlive ultrasound, AGA fetuses between 26 and 37 weeks of gestation demonstrated that mouthing was the most frequent facial expression ( Figure 3A), which is compatible with the previous reports from Japan (Sato et al [14], Kanenishi et al [13], and Yan et al [12]). In contrast to AGA fetus, however, remarkable decrease in the frequency of this mouthing later than 34 weeks in FGR fetuses is the most striking finding in our current study (Tables 5B and 6B, Figures 4B and 5B).…”
Section: Page 7 Ofsupporting
confidence: 93%
“…Recruiting large sample sizes is required in the future study to investigate whether the tendency demonstrated in the present study can be generalized with statistically significant difference. Second, subjective determination to evaluate fetal facial expressions obtained by 4D HDlive ultrasound might lead to inter-observer variability [13,25]. Although relatively good intra-and inter-class correlation coefficients were obtained in the present study, further investigations are required [14,27].…”
Section: Page 7 Ofmentioning
confidence: 58%
See 3 more Smart Citations